Caesalpinbondin A, a Novel Diterpenoid Lactone With an Unprecedented Carbon Skeleton from the Seeds of Caesalpinia bonduc - Fei, Dong-Qing; Li, Hui-Hong; Chen, Xiao-Han; Cui, Wen-Bo; Zhang, Zong-Ping; Zhan, Xiao-Qing; Wang, Mei-Jie; Qi, Feng-Ming; Zhang, Zhan-Xin; Li, Er-Wei (Frontiers in Chemistry, 2022)
Graphical Abstract